Insulin Resistance and Vitamin D Deficiency: A Link Beyond the Appearances - Trimarco, Valentina; Manzi, Maria Virginia; Mancusi, Costantino; Strisciuglio, Teresa; Fucile, Ilaria; Fiordelisi, Antonella; Pilato, Emanuele; Izzo, Raffaele; Barbato, Emanuele; Lembo, Maria; Morisco, Carmine (Frontiers in Cardiovascular Medicine, 2022)
Vitamin D is a steroid hormone that plays a key role in the regulation of body homeostasis, including cardiovascular function. Although the chronic deficiency of vitamin D is associated with cardiovascular risk factors, as well as with an adverse prognosis, randomized controlled trials have failed in demonstrating that dietary vitamin D supplementation could ameliorate the prognosis of patients with cardiovascular diseases, and suggested that vitamin D deficiency is the expression of the effects of other determinants of cardiovascular risk. Thus, the supplementation of vitamin D is not sufficient to improve the cardiovascular risk profile and prognosis. Insulin resistance is a complex phenomenon that plays a key role in the pathogenesis of conventional cardiovascular risk factors. Interestingly, defects of vitamin D and insulin resistance have a superimposable epidemiological distribution. According to the common view, Insulin resistance is considered the direct or indirect consequence of vitamin D deficiency. However, it is also reasonable to speculate that the deficit or the impaired action of vitamin D, in some circumstances, could be the result of the same pathogenic mechanisms responsible of insulin resistance development. In this case, vitamin D deficiency could be considered an epiphenomenon of insulin resistance. Insulin resistance is a reversible condition, being possibly ameliorated by physical activity and hypocaloric diets. Notably, both physical exercise and energy-restricted dietary regimens are associated with an increase of vitamin D levels. These findings indicate that improving insulin resistance condition is a necessary step to ameliorate vitamin D supplementation-based strategies in cardiovascular prevention.